LEGAL PROTECTION FOR MEDICAL PERSONNEL IN PROVIDING ASSISTANCE TO DEMONSTRATION VICTIMS BASED ON LAW NUMBER 12 OF 2005 - Vivi Vibri Yannika Setiana Putri; Gunawan Hadi Purwanto; Asri Elies Alamanda (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2026)
Demonstrations as a manifestation of the right to freedom of expression and peaceful assembly often develop into conflict-prone and injury-prone situations, requiring the presence of medical personnel to provide emergency assistance. In these conditions, medical personnel carry out a neutral and professional humanitarian function, but in practice they often face the risk of violence, intimidation, obstruction of duty, and criminalization. This study aims to analyze the legal protection for medical personnel in providing assistance to victims of demonstrations based on Law Number 12 of 2005 concerning the Ratification of the International Covenant on Civil and Political Rights (ICCPR), as well as to examine its implementation in the national legal system. The research method used is normative legal research with a legislative approach and a conceptual approach, through a literature study on laws and regulations, legal doctrines, and literature related to human rights and the protection of medical personnel. The results of the study show that normatively the legal protection of medical personnel has been regulated in Law Number 17 of 2023 concerning Health and strengthened by the principles of the ICCPR, especially related to the right to life, personal security, and protection from inhuman treatment. However, the implementation of these protections in the context of demonstrations has not been optimal due to general regulations, harmonization between international human rights norms and national security policies, and low understanding of the principles of neutrality of medical personnel. Therefore, it is necessary to strengthen operational regulations, harmonize policies, and raise human rights awareness to ensure effective legal protection for medical personnel in demonstration situations.